A Barbarian in the Garden? Cultural Heritage Seen from the Perspective of Economics - Murzyn-Kupisz, Monika (Journal of Public Governance, 2011)
Until recently, research on cultural heritage seemed to be the unquestioned realm of the humanities. However, the development of the heritage market and the need to consider the benefits of its preservation and contemporary usage from many different viewpoints – not only artistic and historical, but also taking into account the perspective of creation and implementation of public policies and strategies, and the overall context of socio-economic development – calls for an active engagement of economics in its analysis as a specific product in the market. Th e author considers two very important issues with respect to theoretical approaches to cultural heritage seen from the perspective of cultural economics and its specific sub-field of heritage economics: the question of heritage values and public goodscharacteristics of many heritage products.